Effect of 4-1 Soccer Training on Passing Control in Junior Athletics - Muhammad Yusril Saputra; I Made Satyawan; Hendra Mashuri (Physical Education Departement of University PGRI Jombang, 2025)
This study aims to determine the effect of 4-1 soccer training on passing control in Brengkok soccer academy athletes who are shining, the problem in this study is the lack of training methods and variations in passing control training. This research method is quantitative with experimental type by using pretest and post-test model. The subjects of this study were Brengkok soccer academy athletes who were shining with a total of 20 athletes. To determine the sample using random sampling and using ordinal pairing A-B-B-A. The procedure for this research activity includes: (1) Pre-test (2) Group division (3) Treatment (4) Post-test. Data processing using SPSS software version 24, with t test analysis. The results of this study indicate that there is a significant effect of 4-1 training on passing control in Shining Football Academy Brengkok athletes. It is proven that with 4-1 training greatly affects passing control so that athletes are more confident and more compact